Asymmetric Effects of Fiscal and Monetary Policies on Environmental Quality in South Africa - Mashao, Teboho Charles (International Journal of Energy Economics and Policy, 2025)
The effect of fiscal and monetary policies can either improve or worsen environmental quality, depending on how the policies are implemented, this may lead to asymmetrical impacts. Therefore, the aim of this study was to investigate the asymmetric effects of fiscal and monetary policies on environmental quality in South Africa from 1990 to 2023 using the nonlinear autoregressive distributed lag (NARDL) technique. The study found that a positive shock in discount rate has a positive and significant influence on carbon emissions (CO2) in the long run however, a negative shock has an insignificant negative impact. Moreover, economic growth was reported to have a significant positive impact on carbon emissions (CO2) in the long run. A positive shock in government expenditure was found to have a significant and negative influence on carbon emissions (CO2), while a negative shock in government expenditure has a significant positive impact in the long run. The effect of fiscal and monetary policies on environmental quality were found to be asymmetrical in the long run. The reported findings have a significant implication for fiscal and monetary policies in South Africa and other countries with similar economic settings. Both monetary and fiscal policies have a significant influence on environmental quality, policymakers could implement strategies to enhance environmental quality by alleviating carbon emissions (CO2). In addition, policymakers should consider coordinating fiscal and monetary policies to attain decarbonisation.